ASPECTOS ETNOZOOLÓGICOS DA AVIFAUNA DO MUNICÍPIO DE JAÇANÃ, RIO GRANDE DO NORTE E POSSÍVEIS FATORES DE AMEAÇA NA REGIÃO - Barbosa, E. D. O.; Mariano, E. F.; Chaves, M. F. (Revista Nordestina de Zoologia, 2014)
Several studies have already reported that people human who maintain a direct relationship with nature can present a fairly accurate knowledge of the environment in which they live. However, this relationship has promoted some environmental problems by interfering right in the distribution of faunistic populations.This research aiming record the etnoornithological knowledges of residents from rural zone of the Jaçanã - Rio Grande do Norte, Northeastern Brazil. Data were obtained through semi-structured questionnaires to a sample of a total of 40 residents, represented by men and women aged between 21 and 85 years old. From the data obtained was drawn up a checklist containing 92 ethnospecies of birds occurring in the city, belonging to 34 families. Regarding possible threat factors of the occurrence of this group in the region, were cited mainly hunting, the dry season and deforestation. The results presented in this study, demonstrate the importance of recording the knowledge that human populations hold about biodiversity as a fundamental basis for the definition of strategies for conserving biological and cultural.